Identity and Border: Comparative Case of “Re-Bordering and De-Bordering” in Myanmar and Indonesia - Pratisti, Siti Aliyuna; Sudirman, Arfin; lanti, Irman G.; Zahid, Ali (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
Identity, as a symbolic system to interpret the world, plays a significant role in shaping human understanding, including social and political structures. Reid (2010) listed key identity markers, including religion, language, bounded sovereign space, censuses, and names. Ethnicity and religion retain a critical point as identity makers since they precede the nationalist identity–and may as well outlast them. In line with Reid’s argument, Farzana (2017) notes the danger of the process of “us” and “other-ing” in Myanmar as an example of how identity is prone to be manipulated to assist the needs and aspirations of the dominant elites, while at the same time, politically excluded the non-dominant ethnics and communities. This article explores how material ideas of borders connect to immaterial structures. Two formations of borders–Myanmar and Indonesia–are compared with focused on scrutinizing similarities and differences in the formation of the immaterial border between the two countries. Despite showing a palpable hypothesis–Indonesia being a successful case of identity construction, while Myanmar is quite the opposite–, revisiting and reconsidering the concept of ‘Re-bordering and De-bordering’ of the two countries are relevant to add new perspectives on the formation of national identity